12m+23=179

Simple and best practice solution for 12m+23=179 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m+23=179 equation:


Simplifying
12m + 23 = 179

Reorder the terms:
23 + 12m = 179

Solving
23 + 12m = 179

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 12m = 179 + -23

Combine like terms: 23 + -23 = 0
0 + 12m = 179 + -23
12m = 179 + -23

Combine like terms: 179 + -23 = 156
12m = 156

Divide each side by '12'.
m = 13

Simplifying
m = 13

See similar equations:

| 2(3x-1)-3(4x+3)-6=5x-4(4x-1) | | -92+7b=13 | | 9y+3=6(y-7) | | 9/10/69 | | -6(x+4)+4x+7=7x+9 | | 47+13a=164 | | 4w-13=47 | | 25x+35y=6 | | 25x-78=72 | | 8(5s-12)-16(2s+7)=0 | | 5x-(x-3)=-21 | | d/8*-4=-6 | | 14x^2-17=0 | | 38=6(y+7)-8y | | 2x-19=73 | | 6n-27= | | 7x^2+5y=22 | | 11+n=-8 | | Z-5x=7z-9-z | | 7x+22=4x-16 | | 5x-32+y+89=180 | | 4x-16=7x+22 | | (x-3)/2-(4x-1)/6=2/3 | | https://media.edgenuity.com/evresources/3111-01-04/mc012-1.jpg | | x/15=-16 | | 1.1(.2x+1.8)+1.28=-12.14 | | x^2-53x+156=0 | | 9k^2+12k-12=0 | | 4+2(x-3)=2x-1 | | -2x+5+5x=22 | | 2y^2/32x^17 | | 4-3(x+2)=8-10 |

Equations solver categories